PERAN GURU PENDIDIKAN AGAMA ISLAM DALAM MENUMBUHKAN JIWA WIRAUSAHA SISWA - Afdialudin, Zidni (Perwira Journal of Economics & Business, 2023)
This study aims to determine and analyze the role of Islamic religious education teachers in fostering the entrepreneurial spirit of students at SMK Negeri 1 Slawi. This research is qualitative field research with descriptive data analysis. Data collection methods use interviews, observation, and documentation. This study shows that the role of Islamic religious education teachers in fostering the entrepreneurial spirit of students at SMK Negeri 1 Slawi is to direct students' way of thinking about the spirit of entrepreneurship, provide a basic religious understanding of the importance of working for a living, and strengthen the behavior and attitudes and character of entrepreneurs exemplified through the story of Islamic civilization in Islamic history carried out in class when learning Islamic religion and integrating Islamic religious education material with the world of entrepreneurship because many Islamic religious education materials in vocational high schools contain the value and character of the entrepreneurial spirit.